2008
DOI: 10.1364/oe.16.018443
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz line detection by a microlens array coupled photoconductive antenna array

Abstract: We present THz ultrashort pulse detection by a photoconductive antenna array consisting of 16 photoconductive antennas. The efficient excitation of the photoconductive antennas has been realized by a microlens array which generates 16 single spots from the exciting fs-laser beam. This combination of optoelectronics and microoptics improves the detection efficiency by an order of magnitude in comparison to an excitation by a line focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…An early attempt in this direction has been reported by Hermann and coworkers who used an array of eight photoconductive antennas [318]. In 2008 Pradarutti et al demonstrated a line array of 16 elements coupled to a microlens array that generates 16 single spots from the exciting fs-laser beam [319]. Very recently, Picometrix demonstrated a hand-held, high-speed THz-TDS reflection line-scanner [320].…”
Section: Practical Applications For Thz Systemsmentioning
confidence: 99%
“…An early attempt in this direction has been reported by Hermann and coworkers who used an array of eight photoconductive antennas [318]. In 2008 Pradarutti et al demonstrated a line array of 16 elements coupled to a microlens array that generates 16 single spots from the exciting fs-laser beam [319]. Very recently, Picometrix demonstrated a hand-held, high-speed THz-TDS reflection line-scanner [320].…”
Section: Practical Applications For Thz Systemsmentioning
confidence: 99%
“…So a complete THz image has to be recorded. As the development of multipixel THz systems with spectroscopic capabilities is still an ongoing process, [52] we will introduce a technique relying on the rapid scanning of one pixel and a relative movement of the object, the so-called raster scanning imaging.…”
Section: Spectroscopic Imagingmentioning
confidence: 99%
“…A combined sensor would be expected to be laboratory based initially, due to the scanning and source requirements of the terahertz sensor. Recent developments show that the scan speed of the THz sensor can be accelerated using a higher number of detection pixels [30]. Also a more optimized THz-optic would be necessary to get a homogeneous illumination of the sample without stripes in the analyzed data.…”
Section: Article In Pressmentioning
confidence: 99%